Nilai Gotong Royong dalam Tatak Tintoa Serser pada Masyarakat Pakpak Bharat - Trijayanti Siregar (Universitas Negeri Medan, 2016)
Peoples Pakpak called the term dance with the wordTatak. Tatak Tintoa Serser(mangirik page) describes the work to harvest rice from beginning to end. Thisstudy aims to explore the value of mutual cooperation contained in Tatak TintoaSerser views from the variety of motion.The cornerstone of the theory used in this study is an understanding of the valueand the theory of solidarity.Time used in research to address Tatak Tintoa Serser carried out since January2016 to March 2016. The study was conducted in the village of Salak, DistrictSalak, Pakpak Bharat. The population once the sample in this study is a resourceand dancers who controlled the culture and dance. Data collection techniquesincluding observation, interviews, literature study and documentation, which isthen analyzed by qualitative descriptive method.The results obtained are moral values such as solidarity and mutual aid values arereflected through movements that are arranged in Tatak Tintoa Serser namelymotion Mangirik Page, motion Manarsari, motion Erserakan Page, motionMangumpulkan Page and motion carry on the hand Page.